Materinska šola z vidika tečajnice - Kalan, Marija (Obzornik zdravstvene nege, 1979)
Activities of the author, who is a pediatrician, cover also the health education of the future parents. To get acquainted with the contents, extent and quality level of the health education programme organized for expectant mothers and to-be fathers, she completed the maternity school programme located at the Department of Obstetrics and Gynecology, the University Medical Centre of Ljubljana. She gives a detailed presentation of this programme, its excellent organization and high quality level. She stresses the relevant part assumed by the nurses whose ingenuity and devotion make it possible for anyone willing to attend to join the above course.